Memoryless modified symmetric rank-one method for large-scale unconstrained optimization - Modarres, Farzin; Abu Hassan, Malik; Leong, Wah June (Science Publications, 2009)
Problem statement: Memoryless QN methods have been regarded effective techniques for solving large-scale problems that can be considered as one step limited memory QN methods. In this study, we present a scaled memoryless modified Symmetric Rank-One (SR1) algorithm and investigate the numerical performance of the proposed algorithm for solving large-scale unconstrained optimization problems.